1998
DOI: 10.1016/s0006-3495(98)77679-9
|View full text |Cite
|
Sign up to set email alerts
|

A Neutron Reflectivity Study of Polymer-Modified Phospholipid Monolayers at the Solid-Solution Interface: Polyethylene Glycol-Lipids on Silane-Modified Substrates

Abstract: The structure of polymer-decorated phospholipid monolayers at the solid-solution interface was investigated using neutron reflectometry. The monolayers were composed of distearoylphosphatidylethanolamine (DSPE) matrixed with varying amounts of DSPE-PEG (DSPE with polyethylene glycol covalently grafted to its headgroup). Mixed lipid monolayers were Langmuir-Blodgett deposited onto hydrophobic quartz or silicon substrates, previously hydrophobized by chemically grafting a robust monolayer of octadecyltrichlorosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 38 publications
7
81
0
Order By: Relevance
“…Hydrophobic interactions among the alkane components near the gold surface in the systems studied by Tokumitsu et al may account for this difference. Previous neutron reflectivity measurements conducted by Kuhl et al [26] may be compared with our data. Their experiments were conducted with a Q z,max in the range of 0.05 to 0.15, compared to our chosen Q z,max of 0.1 (Fig.…”
Section: Neutron Reflectometrysupporting
confidence: 59%
“…Hydrophobic interactions among the alkane components near the gold surface in the systems studied by Tokumitsu et al may account for this difference. Previous neutron reflectivity measurements conducted by Kuhl et al [26] may be compared with our data. Their experiments were conducted with a Q z,max in the range of 0.05 to 0.15, compared to our chosen Q z,max of 0.1 (Fig.…”
Section: Neutron Reflectometrysupporting
confidence: 59%
“…It is also important to emphasize that while the hydrophobic surfaces used in the experiments presented in Fig. 16 strongly attract the ethylene oxide segments of the PEO chains, there is a very large class of materials in which the PEO is not attracted to the surface, such as lipid surfaces 33,34) . There are two pronounced features that can be seen in Fig.…”
Section: Protein Adsorptionmentioning
confidence: 99%
“…For example, it has been shown that for polyethylene oxide (PEO) in the regime of molecular weights used in biocompatible materials and drug carriers, there is a continuous change of structure from the mushroom to the brush 32) . It has been also found that PEO segments are attracted to hydrophobic surfaces and to the water-air interface but not to lipid surfaces 30,31,33,34) . Furthermore, many of the experimental studies are carried out in the intermediate region of surface coverage between the mushroom and the brush.…”
Section: Introductionmentioning
confidence: 99%
“…5 nm. However, in spite of numerous studies utilizing different polymers, including chemically immobilized or cross-linked hydrogels, 18,19 polymer brushes, 20,21 covalently grafted lipopolymers, 22, 23, 4 24 and polyelectrolyte multilayers, 25,26 there is no quantitative study that highlights how polymer supports would modulate the interfacial interactions.…”
Section: Introductionmentioning
confidence: 99%